Canine visceral leishmaniasis due to Leishmania (L.) infantum chagasi in Amazonian Brazil: comparison of the parasite density from the skin, lymph node and visceral tissues between symptomatic and asymptomatic, seropositive dogs - Lima, Luciana Vieira R.; Carneiro, Liliane Almeida; Campos, Marliane Batista; Chagas, Eujênia Janis; Laurenti, Márcia D.; Corbett, Carlos E.P.; Lainson, Ralph; Silveira, Fernando Tobias (Revista do Instituto de Medicina Tropical de São Paulo, 2010)
Canine visceral leishmaniasis (CVL) is recognizable by characteristic signs of disease and is highly lethal. The infection, however, may be quite inapparent in some seropositive dogs, and this has raised the polemic question as to whether or not such animals can be a source of infection for Lutzomyia longipalpis, the vector of American visceral leishmaniasis (AVL). In this study we have examined 51 dogs with acute CVL from an AVL area in Pará State, northern Brazil, and compared the parasite density, amastigotes of Leishmania (L.) infantum chagasi, in the skin, lymph node and viscera of symptomatic with that of nine asymptomatic but seropositive dogs (IFAT-IgG). Post-mortem biopsy fragments of these tissues were processed by immunohistochemistry, using a polyclonal antibody against Leishmania sp. The X² and Mann Whitney tests were used to evaluate the means of infected macrophage density (p < 0.05). There was no difference (p > 0.05) in the skin (10.7/mm² x 15.5/mm²) and lymph node (6.3/mm² x 8.3/mm²), between asymptomatic and symptomatic dogs, respectively. It was higher (p < 0.05), however, in the viscera of symptomatic (5.3/mm²) than it was in asymptomatic (1.4/mm²) dogs. These results strongly suggest that asymptomatic or symptomatic L. (L.) i. chagasi-infected dogs can serve as a source of infection, principally considering the highest (p < 0.05) parasite density from skin (10.7/mm² x 15.5/mm²), the place where the vetor L. longipalpis takes its blood meal, compared with those from lymph node (6.3/mm² x 8.3/mm²) and viscera (1.4/mm²x 5.3/mm²).